Prediction, operations, and condition monitoring in wind energy - Kusiak, Andrew; Zhang, Zijun; Verma, Anoop (Energy (Oxford), 2013)
Recent developments in wind energy research including wind speed prediction, wind turbine control, operations of hybrid power systems, as well as condition monitoring and fault detection are surveyed. Approaches based on statistics, physics, and data mining for wind speed prediction at different time scales are reviewed. Comparative analysis of prediction results reported in the literature is presented. Studies of classical and intelligent control of wind turbines involving different objectives and strategies are reported. Models for planning operations of different hybrid power systems including wind generation for various objectives are addressed. Methodologies for condition monitoring and fault detection are discussed. Future research directions in wind energy are proposed. •Models and methods applied in wind energy are discussed.•Typology of research models is developed.•Control, condition, and performance monitoring of wind turbine components are highlighted.•Future research directions are outlined.